Profil Konseling Adiksi untuk Pemulihan Pengguna Narkoba di Balai Badan Narkotika Nasional (BNN) - Anisa Ayu Salsabila; Hastiani; Amelia Atika (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2026)
The National Narcotics Agency (BNN) plays a strategic role in addressing drug abuse, one of which is through rehabilitation services that include addiction counseling. This counseling is an essential component in supporting users' recovery from drug dependence. However, addiction counseling at BNN has not been extensively explored, particularly in relation to the service profile, methods used, the role of counselors, and the challenges faced in daily practice. This study aims to describe the profile of addiction counseling carried out at BNN, including the approaches, methods, roles of counselors, and challenges in the rehabilitation process of drug users. The research adopts a qualitative approach using a survey study method, which typically begins with problem identification and the establishment of clear and measurable research objectives, followed by a literature review to build a theoretical framework. Data were collected through interviews, observations, and documentation of rehabilitation services at BNN. The results show that addiction counseling at BNN is implemented in a structured manner, with counselors playing a vital role as companions and facilitators in the recovery process. The main challenges encountered include clients' capabilities, limited resources, and societal perceptions. These findings highlight the need for enhanced and strengthened systemic support in the addiction counseling process. The study concludes with recommendations to strengthen cross-sector collaboration by involving various stakeholders, including civil society organizations, healthcare institutions, and the education sector, in order to create a more integrated and sustainable rehabilitation system.